Long‐lasting, biochemically modified mRNA, and its frameshifted recombinant spike proteins in human tissues and circulation after COVID‐19 vaccination - László G. Boros; Anthony M. Kyriakopoulos; Carlo Brogna; Marina Piscopo; Peter A. McCullough; Stephanie Seneff (Wiley, 2024)
Abstract According to the CDC, both Pfizer and Moderna COVID‐19 vaccines contain nucleoside‐modified messenger RNA (mRNA) encoding the viral spike glycoprotein of severe acute respiratory syndrome caused by corona virus (SARS‐CoV‐2), administered via intramuscular injections. Despite their worldwide use, very little is known about how nucleoside modifications in mRNA sequences affect their breakdown, transcription and protein synthesis. It was hoped that resident and circulating immune cells attracted to the injection site make copies of the spike protein while the injected mRNA degrades within a few days. It was also originally estimated that recombinant spike proteins generated by mRNA vaccines would persist in the body for a few weeks. In reality, clinical studies now report that modified SARS‐CoV‐2 mRNA routinely persist up to a month from injection and can be detected in cardiac and skeletal muscle at sites of inflammation and fibrosis, while the recombinant spike protein may persist a little over half a year in blood. Vaccination with 1‐methylΨ (pseudouridine enriched) mRNA can elicit cellular immunity to peptide antigens produced by +1 ribosomal frameshifting in major histocompatibility complex‐diverse people. The translation of 1‐methylΨ mRNA using liquid chromatography tandem mass spectrometry identified nine peptides derived from the mRNA +1 frame. These products impact on off‐target host T cell immunity that include increased production of new B cell antigens with far reaching clinical consequences. As an example, a highly significant increase in heart muscle 18‐flourodeoxyglucose uptake was detected in vaccinated patients up to half a year (180 days). This review article focuses on medical biochemistry, proteomics and deutenomics principles that explain the persisting spike phenomenon in circulation with organ‐related functional damage even in asymptomatic individuals. Proline and hydroxyproline residues emerge as prominent deuterium (heavy hydrogen) binding sites in structural proteins with robust isotopic stability that resists not only enzymatic breakdown, but virtually all (non)‐enzymatic cleavage mechanisms known in chemistry.